On Symbolic Allegoresis of the First Pythagoreans - Domaradzki, Mikołaj (Peitho. Examina Antiqua, 2013)
The present paper argues that the early Pythagoreans contributed significantly to the development of ancient hermeneutics. The article builds on the assumption that even if the thinkers did not deal with allegoresis directly, the very manner of articulating their thought was, nevertheless, quite conducive to the growth of allegorical interpretation. Thus, at least indirectly, Pythagoreanism must have played an important role in the development of allegoresis. The paper identifies two crucial aspects of Pythagorean influence on the allegorical tradition. Firstly, the Pythagoreans made a very specific use of the poetry of Homer and Hesiod as well as of the traditional mythology in general. Secondly, the teachings of Pythagoras were expressed in terms of various ambiguous symbols that required special exegesis. Both these factors must have contributed considerably to the development of allegoresis: the idiosyncratic use of conventional mythology, on the one hand, and the enigmatic nature of the Pythagorean symbols, on the other, must have provoked extensive search for the latent (i.e., “allegorical”) meaning of the “messages” in question.